Variability of soil organic carbon with elevation gradient in the Yarlung Tsangpo River Basin on the southeastern Tibetan Plateau - Lin, Dian; Xin, Zhongbao; Lin, Feng; Liu, Jinhao; Huang, Yanzhang (International Soil and Water Conservation Research, 2025)
Soil organic carbon (SOC) plays a critical role in the carbon cycle of alpine ecosystems; however, little is known about the dynamics of SOC governed by soil types and elevation gradients in these systems. In this study, soil properties, environmental conditions, and anthropogenic activities were identified along an 835 km east-west transect in the Yarlung Tsangpo River of the Tibetan Plateau region, which has an elevation range of 2800–5200 m. The information was used to investigate the effects of two soil types (dark felty soils and aeolian soils) and elevation gradients on SOC dynamics. The findings revealed that the average SOC content in dark felty soil (15.13 ± 5.78 g/kg) was significantly greater than that in aeolian soil (7.98 ± 2.76 g/kg). The SOC content of dark felty soil continuously increased with elevation, increasing by about 23.4 g/kg for every 1000 m increase in elevation. In contrast, owing to the high sand particle content and loose, porous structure of aeolian soil, the low SOC content did not vary with elevation. We found that mean annual precipitation (MAP), normalized difference vegetation index (NDVI), electrical conductivity (EC), and clay content (clay) were the primary factors influencing SOC accumulation in dark felty soils. As elevation increased, a more humid and cool water-thermal environment was formed, significantly improving vegetation (NDVI) and optimizing soil physicochemical properties (clay and EC). These factors interacted synergistically to promote significant SOC accumulation in dark felty soils. This study emphasized the importance of the effects of dark felty soil and aeolian soil on the SOC content and improved the understanding of the mechanism by which SOC accumulates in the alpine region of high elevation areas. [Display omitted]